Deviance detection by a P3-like response in rat posterior parietal cortex - Imada, Allicia; Morris, Allyn; Wiest, Michael C. (Frontiers in Integrative Neuroscience, 2013)
To better understand sensory processing in frontal and parietal cortex of the rat, and to further assess the rat as a model of human frontal-parietal processing, we recorded local field potentials (LFPs) from microelectrode arrays implanted in medio-dorsal frontal and posterior parietal cortex of awake rats as they were presented with a succession of frequent "standard" tones and infrequent "oddball" tones. Extending previous results from surface recordings we found, after controlling for the frequencies of the standard and oddball tones, that rat frontal and parietal evoked LFPs (eLFPs) exhibit significantly larger N1 (~40ms latency), P2 (~100ms), N2 (~160ms), P3E (~200-240ms), and P3L(~300-500ms) amplitudes after an oddball tone. These neural oddball effects could contribute to the automatic allocation of attention to rare stimuli. To determine whether these enhanced responses to rare stimuli could be accounted for in terms of stimulus-specific neural adaptation (SSA), we also recorded during single-tone control sessions involving frequent standard or infrequent oddball beeps alone. We compared the difference between rare-tone and frequent-tone response amplitudes in the two-tone context (oddball effect) or single-tone context which isolates the contribution of SSA (SSA effect). An analysis of variance revealed a significant main effect of tone context on rare-tone response enhancements, showing that the rare-tone enhancements were stronger in the two-tone context than the single-tone context. This difference between tone contexts was greatest at the early P3E peak (200-240ms post-beep) in parietal cortex, suggesting true deviance detection by this evoked response component, which cannot be accounted for in terms of simple models of SSA.